Return to Play in Elite Contact Athletes After Anterior Cervical Discectomy and Fusion: A Meta-Analysis. (September 2017) - McAnany, Steven J.; Overley, Samuel; Andelman, Steven; Patterson, Diana C.; Cho, Samuel K.; Qureshi, Sheeraz; Hsu, Wellington K.; Hecht, Andrew C.
Study Design: Systematic literature review and meta-analysis of studies published in English language. Objective: Return to play after anterior cervical discectomy and fusion (ACDF) in contact athletes remains a controversial topic with no consensus opinion in the literature. Additional information is needed to properly advise and treat this population of patients. This study is a meta-analysis assessing return to competitive contact sports after undergoing an ACDF. Methods: A literature search of Medline, Embase, and Cochrane Reviews was performed to identify investigations reporting return to play following ACDF in professional contact athletes. The pooled results were performed by calculating the effect size based on the logic event rate. Studies were weighted by the inverse of the variance, which included both within and between-study error. Confidence intervals (CIs) were reported at 95%. Heterogeneity was assessed using the Q statistic and I 2 . Sensitivity analysis and publication bias calculations were performed. Results: The initial literature search resulted in 166 articles, of which 5 were determined relevant. Overall, return to play data was provided for 48 patients. The pooled clinical success rate for return to play was 73.5% (CI = 56.7%, 85.8%). The logit event rate was calculated to be 1.036 (CI = 0.270, 1.802), which was statistically significant ( P = .008). The studies included in this meta-analysis demonstrated minimal heterogeneity with Q value of 4.038 and I 2 value of 0.956. Conclusions: Elite contact athletes return to competition 73.5% of the time after undergoing ACDF. As this is the first study to pool results from existing studies, it provides strong evidence to guide decision making and expectations in this patient population.